Factor Xa Inhibitor-Related Intracranial Hemorrhage: Results From a Multicenter, Observational Cohort Receiving Prothrombin Complex Concentrates. Issue 21 (26th May 2020) - Panos, Nicholas G.; Cook, Aaron M.; John, Sayona; Jones, G. Morgan
Abstract : Background: Since the approval of the oral factor Xa inhibitors, there have been concerns regarding the ability to neutralize their anticoagulant effects after intracranial hemorrhage (ICH). Multiple guidelines suggest using prothrombin complex concentrates (PCCs) in these patients on the basis of research that includes a limited number of patients with ICH. Given this, we aimed to evaluate the safety and efficacy of PCCs for factor Xa inhibitor–related ICH in a large, multicenter cohort of patients. Methods: This was a multicenter, retrospective, observational cohort study of patients with apixaban- or rivaroxaban-related ICH who received PCCs between January 1, 2015, and March 1, 2019. The study had 2 primary analysis groups: safety and hemostatic efficacy. The safety analysis evaluated all patients meeting inclusion criteria for the occurrence of a thrombotic event, which were censored at hospital discharge or 30 days after PCC administration. Patients with intracerebral, subarachnoid, or subdural hemorrhages who had at least 1 follow-up image within 24 hours of PCC administration were assessed for hemostatic efficacy. The primary efficacy outcome was the percentage of patients with excellent or good hemostasis on the basis of the modified Sarode criteria. Secondary outcomes included an evaluation of in-hospital mortality, length of stay, infusion-related reactions, and thrombotic event occurrence during multiple predefined periods. Results: A total of 663 patients were included and assessed for safety outcomes. Of these, 433 patients met criteria for hemostatic efficacy evaluation. We observed excellent or good hemostasis in 354 patients (81.8% [95% CI, 77.9–85.2]). Twenty-five (3.8%) patients had a total of 26 thrombotic events, of which 22 occurred in the first 14 days after PCC administration. One patient had documentation of an infusion-related reaction. For the full cohort of patients, in-hospital mortality was 19.0%, and the median intensive care unit and hospital lengths of stay were 2.0 and 6.0 days, respectively. Conclusions: Administration of PCCs after apixaban- and rivaroxaban-related ICH provided a high rate of excellent or good hemostasis (81.8%) coupled with a 3.8% thrombosis rate. Randomized, controlled trials evaluating the clinical efficacy of PCCs in patients with factor Xa inhibitor–related ICH are needed. Abstract : Supplemental Digital Content is available in the text.